Sex differences in the relationships between body dissatisfaction, quality of life and psychological distress. (3rd July 2016) - Griffiths, Scott; Hay, Phillipa; Mitchison, Deborah; Mond, Jonathan M.; McLean, Siân A.; Rodgers, Bryan; Massey, Robin; Paxton, Susan J.
Abstract: Background : Body dissatisfaction is associated with impairment in women's quality of life (QoL). To date, research has not examined the relationship between body dissatisfaction and men's QoL, or sex differences in this relationship. Methods : A community sample of 966 males and 1, 031 females living in Australia provided information about their body dissatisfaction, mental health and physical health‐related QoL, and eating disorder symptoms. Data were analysed using three hierarchical multiple regressions and interactions between body dissatisfaction and sex were examined. Results : For both sexes, increasing levels of body dissatisfaction were associated with poorer mental and physical health‐related QoL and greater psychological distress. The adverse associations between body dissatisfaction and mental health‐related QoL, and between body dissatisfaction and psychological distress, were more pronounced for males. Conclusion : High levels of body dissatisfaction may threaten the psychological and physical wellbeing of both men and women. Body dissatisfaction appears to be a public health problem, distinct from the eating disorders and other adverse psychological phenomena for which body dissatisfaction is commonly discussed as a risk factor. Males, historically understudied and underrepresented in body image research, warrant increased empirical attention.